2021
DOI: 10.3390/ijms221810100
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict the Isosymmetric Phase Transition? Application of DFT Calculations to Study the Pressure Induced Transformation of Chlorothiazide

Abstract: Isosymmetric structural phase transition (IPT, type 0), in which there are no changes in the occupation of Wyckoff positions, the number of atoms in the unit cell, and the space group symmetry, is relatively uncommon. Chlorothiazide, a diuretic agent with a secondary function as an antihypertensive, has been proven to undergo pressure-induced IPT of Form I to Form II at 4.2 GPa. For that reason, it has been chosen as a model compound in this study to determine if IPT can be predicted in silico using periodic D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, none of them have been observed; this could be possibly caused by a too-short simulation time, 20 ps, or an inadequate level of theory. However, during our previous studies [34,35], we have found that major changes accompanying polymorphic phase transitions occur during the first few picoseconds of simulations. However, in those mentioned cases, we have performed the MD simulations at the DFT level using CASTEP due to the significantly smaller unit cells in those previous studies.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 76%
“…However, none of them have been observed; this could be possibly caused by a too-short simulation time, 20 ps, or an inadequate level of theory. However, during our previous studies [34,35], we have found that major changes accompanying polymorphic phase transitions occur during the first few picoseconds of simulations. However, in those mentioned cases, we have performed the MD simulations at the DFT level using CASTEP due to the significantly smaller unit cells in those previous studies.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 76%
“…One of the solutions to the aforementioned problem can be the application of ab-initio molecular dynamics (aiMD) to include the kinetic energy factor in the phase transition [ 39 ]. For example, based on experimental findings, chlorothiazide, a diuretic agent, has been proven to undergo pressure-induced isosymmetric structural phase transition (IPT) of Form I to Form II at 4.2 GPa ( Figure 4 ) [ 102 ].…”
Section: The Classes Of Modeled Systemsmentioning
confidence: 99%
“…For example, based on experimental findings, chlorothiazide, a diuretic agent, has been proven to undergo pressure-induced isosymmetric structural phase transition (IPT) of Form I to Form II at 4.2 GPa ( Figure 4 ) [ 102 ]. The authors of the work [ 39 ] performed geometry optimization calculations of Form I and Form II at all experimentally studied pressure conditions to simulate compression (when geometry optimization starts from Form I) or decompression (when geometry optimization starts from Form II) using two functionals: PBE TS and PBESOL. The next stage was to measure the root mean square deviation (RMSD) values between the estimated and experimental crystal structures in order to assess the correctness of the modeled structures.…”
Section: The Classes Of Modeled Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research interest in the properties of molecular crystals under high pressure has continued to rise. , External high pressure reduces intermolecular distances, enhances intermolecular and intramolecular interactions, modifies properties, and induces structure phase transformation in molecular crystals . High-pressure research methods typically include both experimental and computational components. The experimental method based on diamond anvil cells (DAC) generates a high-pressure environment for a sample and can provide the evolution of phase transitions, atomic coordinates, and unit cell parameters of molecular crystals, combined with synchrotron XRD, Raman and infrared spectroscopy, photoluminescence, etc. Computational methods, including density functional theory (DFT) and force field (FF) groups, can provide the energetic characteristics of investigated materials and explain the nature of phase transitions on the basis of the critical parameters from experimental measurements for molecular crystals. , Significant progress in engineering made these experiments possible and even routine in some sense, but they were still very time-consuming and complicated. These experiments give the atomic coordinates and cell parameters of molecular crystals.…”
Section: Introductionmentioning
confidence: 99%